FEATURES OF DECENTRALIZATION IN THE UK: EXPERIENCE OF INTERACTION BETWEEN THE GOVERNMENT AND CIVIL SOCIETY FOR UKRAINE - Olha Andrieieva; Nataliia Larina; Yurii Ruban (Публічне управління та регіональний розвиток)
The article establishes that Brexit has put decentralization in the UK under serious threat. It is stated that there is a sharp gap between the way decentralization agreements are interpreted in Westminster and the way they are interpreted in Wales, Scotland and Northern Ireland. Brexit has caused serious divisions between the main ruling parties in Northern Ireland - Sinn Féin, which heads the regional government and advocates a reunited Ireland, and the Democratic Unionist Party (DUP), which advocates the region remaining within the UK. The article explores how the UK governments could conclude new UK-wide agreements. The focus is on the environment, agriculture and fisheries, three policy areas in which the powers devolved to the regions in the process of decentralization are in significant conflict with post-Brexit EU law.